Sabendo que A = {a,b,c,d} e B = {b} , a sentença verdadeira é:
a)( ) An B = A
b) ( ) A B = 0
c) ( )AUB = A
d) ( ) AU B = 0
Anexos:
![](https://pt-static.z-dn.net/files/dee/43ee9af84950ce4dd398dcdaf332e0a7.jpg)
Soluções para a tarefa
Respondido por
3
Resposta:
C
Explicação passo-a-passo:
AUB = A
ou seja, o que esta em A + o que esta em B
ou seja {a b c d}
como A = {a b c d}
AUB = A
fazanoconsultor:
muito obrigado
Perguntas interessantes
Matemática,
10 meses atrás
História,
10 meses atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás
História,
1 ano atrás
Ed. Física,
1 ano atrás